Предмет: Математика, автор: tugolukovanast

Помогите решить, пожалуйста

Приложения:

Ответы

Автор ответа: YuriyYarema
0
( frac{5}{18}- frac{7}{12}*0.5 ): frac{5}{18} - frac{2}{3}=

 (frac{5}{18}- frac{7}{12}*0.5 ): frac{5}{18} - frac{2}{3}=
 \ 1)  -frac{7}{12} * frac{5}{10} =  frac{35}{120} = - frac{7}{24}   
 \ 2) frac{5}{18}- (- frac{7}{24})= frac{20+21}{72} =  frac{41}{72} 
 \ 3)  frac{41}{72} : frac{5}{18}=  frac{41}{72} * frac{18}{5}  =  frac{41}{20}
 \ 4)  frac{41}{20}- frac{2}{3}=  frac{123-40}{60}=       frac{83}{60}.

Автор ответа: YuriyYarema
0
ну ёмаёё
Похожие вопросы
Предмет: Алгебра, автор: Аноним